Go well, stay well - Jones, Toeckey (New York Harper & Row, 1980)
A white girl in South Africa finds out how difficult it is to be friends with a black girl.
Keywords: Friendship -- Fiction; Race relations -- Fiction; South Africa -- Race relations -- Fiction